Comparative Evaluation of Three Preprocessing Methods for Extraction and Detection of Influenza A Virus Nucleic Acids from Sputum - Yu, Fei; Qiu, Ting; Zeng, Ying; Wang, Yiyin; Zheng, Shufa; Chen, Xiao; Chen, Yu (Frontiers in Medicine, 2018)
Viscous sputum specimens usually cannot undergo automated extraction, and thus, a pre-homogenization process is desirable before isolating nucleic acids for real-time reverse transcription PCR. In this study, we compared three preprocessing methods [preprocessing with normal saline (NS), dithiothreitol (DTT), and proteinase K (PK)] of sputum specimens on the extraction and detection of influenza A virus (IAV) nucleic acids. Based on the experimental results of 217 specimens, we found that DTT and PK could be used to improve the homogenization effects of sputum and increase the positive rates by 5.53–6.91% higher than that of the NS group. Comparison of 49 positive specimens in all of the three groups demonstrated that the threshold cycle values of the DTT group and PK group were significantly lower and their nucleic acid concentration and A260/A280 ratio within 1.8–2.0 were higher than those of the NS group. Thus, sputum homogenization before nucleic acid extraction is essential for the accurate diagnosis of IAV infection.